Analisis deskriptif kualitas eksterior dan interior telur Itik Pajajaran - Ai Nurfaridah; Yogi Alatas; Wahyu Suradi Pranata; Yuga Suwarsa; Rizki Prasetiady; Asep Rahmat Khaerudin (Fakultas Pertanian Universitas Majalengka, 2025)
Pajajaran ducks are among the leading local duck breeds with development potential, but comprehensive data on the quality of their eggs remains limited. This study aims to examine the characteristics of the interior and exterior quality of Pajajaran duck hatching eggs. A total of 60 eggs were analyzed using a descriptive method. The results showed that the eggs have a uniform shape (Shape Index 79.08%; Coefficient of variation 3.38%), are predominantly blue-shelled (58.3%), and have a 96.7% fine-shell surface. Average egg weight was 75.75 g, with a proportion of yolk of 28.7 g and albumen of 34.9 g, and . The interior quality is characterized by a Haugh Unit value of 84.61 (AA/excellent category), yolk color 11.26 (deep orange category), yolk index 0.36, and albumen index 0.09. The study concluded that Pajajaran duck eggs have excellent exterior and interior quality and uniformity, making them a potential, superior hatching egg material to support sustainable breeding programs.